2016
DOI: 10.1111/ijpo.12190
|View full text |Cite
|
Sign up to set email alerts
|

Increased brain cortical thickness associated with visceral fat in adolescents

Abstract: SummaryBackground: There has been a growing amount of evidence indicating that excess visceral fat is associated with alterations in brain structure and function, including brain cortical thinning in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 14 publications
2
43
3
Order By: Relevance
“…However, our results are not in line with other work exploring cortical thickness changes related to BMI in teenagers. To date, two studies did not find an association between BMI and cortical thickness [17,18]. The discrepancy between our results and these works could be explained by the age range of the sample, especially the upper age limit, because while both studies included adolescents not older than 18, we included participants in late adolescence, which comprises a stage between 18 and 21 years [45].…”
Section: Associations Between Cortical Gray Matter and Bmicontrasting
confidence: 85%
See 3 more Smart Citations
“…However, our results are not in line with other work exploring cortical thickness changes related to BMI in teenagers. To date, two studies did not find an association between BMI and cortical thickness [17,18]. The discrepancy between our results and these works could be explained by the age range of the sample, especially the upper age limit, because while both studies included adolescents not older than 18, we included participants in late adolescence, which comprises a stage between 18 and 21 years [45].…”
Section: Associations Between Cortical Gray Matter and Bmicontrasting
confidence: 85%
“…Both areas belong to the dorsolateral prefrontal cortex (DLPFC). As far as we know, only Saute and colleagues [18] examined the possible association between adolescents' surface area and BMI. They did not find a relationship between surface area and BMI in 44 teenagers from 15 to 18.…”
Section: Associations Between Cortical Gray Matter and Bmimentioning
confidence: 99%
See 2 more Smart Citations
“…12 Using T2MR, previous in vivo studies using this technique have shown that T2 signal is increased in the MBH of adult humans in association with obesity 2,12,13 and insulin resistance, 12 which also suggests potential implications of hypothalamic gliosis for glucose regulation. 12 Correspondingly, distinct MRI approaches have been used to demonstrate abnormalities in obesity for both the brain's macrostructure (eg, cortical thickness and regional volume) 14,15 and functionality. [16][17][18] For example, functional MRI (fMRI) studies in adults with obesity suggest a disrupted hypothalamic response to glucose ingestion characterized by an attenuated response after glucose intake.…”
mentioning
confidence: 99%